2015
DOI: 10.1523/jneurosci.4882-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Parietal Cortex in the Representation of Task-Reward Associations

Abstract: Rewards obtained from specific behaviors can and do change across time. To adapt to such conditions, humans need to represent and update associations between behaviors and their outcomes. Much previous work focused on how rewards affect the processing of specific tasks. However, abstract associations between multiple potential behaviors and multiple rewards are an important basis for adaptation as well. In this experiment, we directly investigated which brain areas represent associations between multiple tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 55 publications
5
56
1
1
Order By: Relevance
“…Consistent with the results of previous fMRI decoding studies (Etzel et al, 2016;Qiao, Zhang, Chen, & Egner, 2017;Woolgar et al, 2011;Waskom et al, 2014;Wisniewski et al, 2015), RSA successfully tracked neural representations for task rule information. In using this approach, our results replicate the fMRI findings of Etzel et al (2016) in human electroencephalographic data, showing that high reward prospect increased average task coding prior to target onset, and that the difference in task coding between reward conditions was associated with improvements in cognitive performance.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with the results of previous fMRI decoding studies (Etzel et al, 2016;Qiao, Zhang, Chen, & Egner, 2017;Woolgar et al, 2011;Waskom et al, 2014;Wisniewski et al, 2015), RSA successfully tracked neural representations for task rule information. In using this approach, our results replicate the fMRI findings of Etzel et al (2016) in human electroencephalographic data, showing that high reward prospect increased average task coding prior to target onset, and that the difference in task coding between reward conditions was associated with improvements in cognitive performance.…”
Section: Discussionsupporting
confidence: 86%
“…These findings indicated the frontal and temporal lobes illus- The age showed a significantly negative effect on the whole brain diversity, further regional diversity analysis revealed the significantly negative age effect distributed in the right inferior frontal gyrus, right amygdala, right hippocampus, left parahippocampal cortex, and left inferior parietal gyrus. The inferior parietal gyrus was thought to show a remarkable flexibility in task demands (Wisniewski, Reverberi, Momennejad, Kahnt, & Haynes, 2015). The amygdalahippocampus circuit has been reported to be related with response switching (Cohen, Elger, & Weber, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The inferior frontal gyrus was reported to be the key region related with earlier preparatory stages of set-shifting (Perianez et al, 2004). The inferior parietal gyrus was thought to show a remarkable flexibility in task demands (Wisniewski, Reverberi, Momennejad, Kahnt, & Haynes, 2015). Thus the decreased brain diversity in these regions might response to the declines of cognitive flexibility in elderly (Wecker, Kramer, Hallam, & Delis, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the reward group, the expected value for monetary rewards was in conflict with the intrinsic value for the difficult task, and participants had to accommodate these opposing values. Supporting this idea, a previous fMRI study showed that the inferior parietal lobule is related to expected large future rewards at the cost of immediate losses (Tanaka et al, 2004), suggesting the possibility that this area is activated when different sources of rewards are in conflict and thus need to be integrated (see also Wisniewski et al, 2015).…”
Section: Discussionmentioning
confidence: 87%